1999
DOI: 10.1007/s003300050680
|View full text |Cite
|
Sign up to set email alerts
|

Phyllodes tumors of the breast

Abstract: The aim of this study was to describe the clinical, mammographic, and sonographic findings of phyllodes tumor of the breast and correlate them to the benign or malignant pathological nature of the lesion and its clinical behavior. We retrospectively reviewed the clinical, radiologic, and pathologic findings of 12 cases of phyllodes tumors diagnosed in our hospital in the past 6 years, 6 of which were malignant. The surgical management and clinical course of the patients were also reviewed. Mammographically, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 11 publications
(12 reference statements)
3
14
0
Order By: Relevance
“…The posterior acoustic enhancement phenomenon is a sonographic feature that has been observed in 50-77% of phyllodes tumors in different studies [9,14]. This is explained by the presence of intramural cysts representing areas of degeneration and focal necrosis [15,19]. In accordance with the literature, posterior acoustic enhancement was more commonly detected in phyllodes tumors than in fibroadenomas in the present study (supplemental fig.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The posterior acoustic enhancement phenomenon is a sonographic feature that has been observed in 50-77% of phyllodes tumors in different studies [9,14]. This is explained by the presence of intramural cysts representing areas of degeneration and focal necrosis [15,19]. In accordance with the literature, posterior acoustic enhancement was more commonly detected in phyllodes tumors than in fibroadenomas in the present study (supplemental fig.…”
Section: Discussionsupporting
confidence: 81%
“…Some groups reported that phyllodes tumors are frequently lobulated in shape [14,15] while others found no significant difference in shape between fibroadenomas and phyllodes tumors. Both tumors tend to be oval or lobulated in shape [6,8,9,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly to previous studies, the heterogeneous echo pattern was a significantly frequent B-mode US feature in PTs, which might reflect their stromal heterogeneity or internal cystic structures [10,34,35]. However, the heterogeneous echo pattern cannot be regarded as specific or pathognomonic for PTs, because it can be observed in a substantial number of FAs (13.5–51%) [10,34].…”
Section: Discussionsupporting
confidence: 62%